2012
DOI: 10.1186/1824-7288-38-7
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular distraction in neonates: indications, technique, results

Abstract: BackgroundThe Pierre Robin Sequence features were first described by Robin in 1923 and include micrognathia, glossoptosis and respiratory distress with an incidence estimated as 1:8,500 to 1:20,000 newborns. Upper airway obstruction and feeding difficulties are the main concerns related to the pathology. Mandibular distraction should be considered a treatment option (when other treatments result inadequate).Patiants and methodsTen patients between the ages of 1 month and 2 years with severe micrognathia and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 32 publications
1
24
0
8
Order By: Relevance
“…(12). A previous study on children with severe micrognathia and airway obstruction undergoing bilateral mandibular distraction revealed improvement in respiratory distress when other procedures have failed (13). Several studies in agreement with our finding demonstrated the improvement of mouth opening with distraction osteogenesis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(12). A previous study on children with severe micrognathia and airway obstruction undergoing bilateral mandibular distraction revealed improvement in respiratory distress when other procedures have failed (13). Several studies in agreement with our finding demonstrated the improvement of mouth opening with distraction osteogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Xiaofeng et al ., describe distraction osteogenesis as a reliable surgical method to alleviate the narrow upper airway in growing OSA patients, especially those with severe craniomaxillomandibular deformities . A previous study on children with severe micrognathia and airway obstruction undergoing bilateral mandibular distraction revealed improvement in respiratory distress when other procedures have failed .…”
Section: Discussionmentioning
confidence: 97%
“…With the advancement of miniaturized intraoral distractors, the distraction osteogenesis technique has drastically transformed the concept of correction of maxillofacial deformities [3][4][5][6][7], having multiple advantages over extraoral distractors, considering the patient's better acceptance and compliance during the activation and consolidation phases because they are discrete and easy to handle, the reduction of the scar of the skin caused by the traction of transcutaneous fixation pins, preventing injury to the neurovascular bundles, allowing the invisible distraction of the jaw, thus eliminating frequent monitoring and limitation in social life and improving the stability of the attachment to the bone [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…As the technique evolved, other technologies have been developed and associated with surgical procedures, increasing predictability and final stability, as well as facilitating planning [27,28]. In 2010, Feiyun P et al, [8] described the use of three-dimensional craniofacial models in the planning of simultaneous surgical correction of atm ankylosis associated with mandibular micrognathia.…”
Section: Do In the Treatment Of Atm Ankylosis Associated With Micrognmentioning
confidence: 99%
“…Even though an acceleration is observed in the postnatal period, in cases with 24 . demonstrated the benefit from mandibular distraction in PRS patients for relieving airway problems and preventing tracheotomy procedure.…”
Section: Discussionmentioning
confidence: 99%